Pandalungan as a Social Identity: Identity Construction, Migration, and Cultural Negotiation in Jember - Vivi Sri Rafika Umroh; Kunawi Basyir (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This article examines the construction of Pandalungan cultural identity in Jember as a product of interaction, acculturation, and cultural negotiation between the Madurese and Javanese communities. Employing a qualitative approach with an acculturative anthropological perspective, the study explores how migration, social interaction, social construction, cultural acculturation, and identity negotiation have shaped the formation of Pandalungan identity. Data were collected through in-depth interviews with cultural figures, historians, and community leaders representing the Pandalungan community in Jember, complemented by a review of relevant literature. The analysis draws upon Peter L. Berger's theory of social construction, the cultural acculturation models of the Melting Pot and Salad Bowl, and Homi K. Bhabha's concept of cultural hybridity. The findings reveal that the social construction of Pandalungan culture has evolved through Berger's three dialectical processes-externalization, objectification, and internalization-resulting in a hybrid culture with distinctive characteristics reflected in language, social traditions, religious rituals, social structures, and shared values. Furthermore, the official declaration of Jember as the